'"They Think We're Just Ghetto, But Nah!": Re‐Working Young People's Presence. (7th April 2021) - Aitken, Stuart C.; Pearson, Elliot; Herman, Thomas
ABSTRACT: With this paper, we document aspects of a year‐long project with 11th‐grade students from a high school in City Heights, San Diego. The students chose to become present, to share their experiences, explore others' understandings of their neighborhood, and collaborate to create an online multi‐media narrative that reflected them and their relations to the neighborhood. Theoretically, we involve a transversal politics that embrace young people's multiplicities of relations. We assume multiculturalism as a foil to engage young people's community presence. We show how the project moved toward a vibrant, layered, networked, and lyrical presence for young people in City Heights.